A Compact, Low Loss, and Broadband Two-Section Lumped-Element Wilkinson Power Combiner Using 130 nm SiGe HBT BiCMOS Technology - Ju, Inchan; Cressler, John D. (GSMM 2022 - 14th Global Symposium on Millimeter-Waves and Terahertz, 2022)
This paper presents a compact, low loss two-section lumped-element Wilkinson power combiner (WPC) supporting a decade bandwidth of2-20 GHz. Each λ/4 impedance transformer, necessary for implementing the WPC, is realized by four cascaded C-L-C π-networks that is embedded into a single 3-turn symmetric inductor. It achieves compact size, high passive efficiency, and high L-C cut-off frequency (fc) simultaneously. The design procedure of the λ/4 impedance transformer is described in detail. The prototype WPC was fabricated in 130 nm SiGe HBT BiCMOS technology, with an active area of 0.34 × 0.36mm2. The proposed two-section lumped element WPC attained the minimum insertion loss of 0.65 dB and its passive efficiency remains higher than 63% at 20 GHz. Return losses and isolation are higher than 10.0 and 7.0 dB, respectively, from 2 to 20 GHz.
Keywords: BiCMOS; Broadband; Combiner; Inductor; Lumped; Mm waves; Phased-arrays; Transformer; Wide-band; Wilkinson; BiCMOS; broadband; combiner; inductor; lumped; millimeter-wave; mmWave; phased array; power amplifier; SiGe; transformer; wideband; Wilkinson